Development of new biomaterials with antibacterial properties for future application in regenerative medicine - Vieira, Tânia Sofia dos Santos (2013)
Submitted by Helena Fortuna (hfortuna@ubi.pt) on 2013-03-25T14:56:39Z No. of bitstreams: 1 Tese_Tânia Vieira.pdf: 3066329 bytes, checksum: 9a9f4c643d04a6277e31951256bbf31d (MD5)